Calcium-binding protein S100A7 and epidermal-type fatty acid-binding protein are associated in the cytosol of human keratinocytes. - Hagens, G (1999)
Expression of epidermal-type fatty acid-binding protein (E-FABP) and S100A7 has previously been shown to be elevated in psoriatic skin, a disease characterized by abnormal keratinocyte differentiation. However, no causal relationship between the up-regulation of these proteins and the disease has been shown. E-FABP is thought to be involved in cytosolic fatty acid (FA) transport, whereas the role of S100A7 is still unknown. In this report, we show by overlay assays that E-FABP, immobilized on nitrocellulose, is able to capture S100A7 from cytosolic psoriatic protein extracts and vice versa, suggesting the formation of a complex between the two proteins. Using purified E-FABP and S100A7, the complex can be reconstituted only in presence of EDTA. Moreover, we show that increased EDTA concentrations in psoriatic cytosolic protein extracts enhance complex formation. Partial complex disruption was obtained by the addition of physiological concentrations of Zn2+ (0.1 mM), whereas Ca2+ at 5 mM and Mg2+ at 30 mM had no effect. On the other hand, high Ca2+ concentrations (30 mM) resulted in partial complex disruption. Oleic acid-binding properties were observed for free E-FABP and the complex E-FABP-S100A7, but not for free S100A7. By using confocal microscopy we show that S100A7 and E-FABP are co-localized in the cytoplasm of differentiating keratinocytes from lesional psoriatic skin. These data indicate that formation of the E-FABP-S100A7 complex and its FA-binding function might be regulated at least by bivalent cations.